PENGARUH BRAND IMAGE, PROMOSI, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN MASYARAKAT KLUNGKUNG DALAM ERA DIGITAL MENGGUNAKAN APLIKASI GRABFOOD - I Putu Dede Dian Pratama; Ni Putu Nita Anggraini; I Wayan Gede Antok Setiawan Jodi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
The aim of this research is to determine and explain the influence of brand image, promotions and price perceptions on Klungkung people's purchasing decisions in the digital era using the Grabfood application. This research uses quantitative methods. This research was conducted in Klungkung Regency and Grabfood users in Klungkung Regency are the population in this study whose exact number is not known. The sample size was determined 5 times the number of indicators so that a sample of 80 respondents was obtained. Primary data collection was carried out using a questionnaire. Hypothesis testing was carried out using multiple linear regression analysis. Based on the results of the analysis, it can be concluded that: 1) brand image has a positive and significant effect on purchasing decisions, 2) promotion has a positive and significant effect on purchasing decisions, 3) price perception has a positive and significant effect on purchasing decisions. In order to improve purchasing decisions, Grabfood is expected to be able to increase food or drink choices by expanding area coverage, increasing promotions with a longer intensity and increasing competitiveness in the form of low prices or providing price discounts.